Doping effects on the thermoelectric properties of pristine poly(3, 4-ethylenedioxythiophene). Issue 43 (14th May 2015) - Zhang, Biao; Wang, Kan; Li, Dongde; Cui, Xudong
<x xml:space="preserve">Abstract</x> Electronic and thermoelectric properties of poly(3, 4-ethylenedioxythiophene) (PEDOT) depend strongly on its geometric structure and the free charge concentration in the PEDOT crystals.